Pragmatic Comprehension Deficit in Parkinson's Disease - Holtgraves, Thomas (2009)
Recognizing the specific speech act (Searle, 1969) that a speaker performs with an utterance is a fundamental feature of pragmatic competence. However, little is known about neurocognitive mediation of speech act comprehension. The present research examined the extent to which people with Parkinson's Disease (PD) comprehend specific speech acts. In the first experiment, participants read conversational utterances and then performed a lexical decision task (decide whether a target string of letters is a word). Consistent with past research, non-impaired participants performed this task more quickly when the target string was the speech act associated with the preceding utterance. In contrast, people with Parkinson's disease did not demonstrate this effect, suggesting that speech act activation is slowed or is not an automatic component of comprehension for people with PD. In a second study, participants were given unlimited time to indicate their recognition of the speech act performed with an utterance. PD participants were significantly poorer at this task than were control participants. We conclude that a previously undocumented language disorder exists in PD and that this disorder involves a selective deficit in speech act comprehension. Frontostriatal systems (the systems impaired in PD) likely contribute to normal speech act comprehension.